Design, Manufacturing, and Commissioning of BIRCAM (Bootes InfraRed CAMera) - Alberto Riva; Paolo Conconi; Alberto Javier Castro-Tirado; Filippo Zerbi; Ronan Cunniffe; Martin Jelinek; Stanislav Vìtek (Advances in Astronomy)
This paper covers the various aspect of design, manufacturing and commissioning of the infrared camera BIRCAM, installed at BOOTES-IR, the 60 cm robotic infrared telescope at Sierra Nevada Observatory (OSN, Granada, Spain). We describe how we achieved a quality astronomical image, moving from the scientific requirements.